SURVEY TINJAU KUALITAS BATUBARA KABUPATEN SORONG PROVINSI PAPUA BARAT - Eric A. Patandianan (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
Data and information on mineral and energy resources have a very important role in supporting of the regional development and business activities in the mining sector nationally. One of the locations of coal sources is in the Sorong Regency Area, specifically at the “M” and “N” Districts. For this reason, an initial exploration activity is needed in the form of a review survey to find the availability, distribution and quality of coal in both districts. As part of the inventory and information on coal resource data for regional governments in managing and utilizing sustainable regional development in Sorong and West Papua Province in general, the data are important. The coal sources is located at the Klasaman Formation in “M” District and the Sele Conglomerate Formation in “N” District. In “M” District the thickness of the coal on the surface is quite thick, ranging from ± 45 - 110 cm with the direction of the southwest and southeast while the Coal Outcrop in the District of “N” has a thickness of 60-100 cm on the surface with north-eastward direction. Based on the results of the Proximate Analysis it was concluded that the quality of coal in the “M” District was included in the